THE EFFECT OF FINANCIAL COMPENSATION AND SKILL ON EMPLOYEE PERFORMANCE AT PT. MITRA BUMI BUKIT SEMBILAN BANGKINANG REGENCY - M. Ilhamdhi Akbar; Syamsul Bahri; Yulizar Baharuddin (Jurnal Riset Manajemen Indonesia, 2021)
This study aims to determine the effect of financial compensation and skills on employee performance at PKS PT. Mitra Bumi Bukit Sembilan Bangkinang District. The population in this study were all employees at PT. Mitra Bumi Bukit Sembilan Bangkinang District. The sample of this study used the Slovin formula technique so that the sample in this study was 56 employees of PKS PT. Mitra Bumi Bukit Sembilan, Bangkinang District. The data collection techniques used were questionnaires and research files. The data analysis technique used is multiple linear regression analysis with a significant level (α) of 0.05. The results of this study concluded that skills have a significant partial effect on performance, with a significant value greater than 0.05. The results of the analysis of this study indicate that financial compensation and skills simultaneously have a significant effect on employee performance at PT. Mitra Bumi Bukit Sembilan, Bangkinang District. There is a very strong relationship between financial compensation and skill variables on employee performance at PKS PT. Mitra Bumi Bukit Sembilan Bangkinang District.